Community Pharmacist in Dementia Care: A New Avenue in Community Pharmacy Practice: An Indian Perspective - Dhananjayan, Karthik (Indian Journal of Pharmacy Practice, 2026)
Dementia is a critical and growing public health challenge in India, with cases projected to triple by 2050. This crisis is exacerbated by a fragmented healthcare system, a severe shortage of specialists, and profound social stigma. As one of the most accessible and trusted health care professionals, Community Pharmacists (CPs) are a vital yet underutilized resource can become a cornerstone of community-based dementia support. This article identifies challenges in dementia care and highlights the opportunities for CPs to bridge the dementia care gap. CPs can adopt a multi-faceted role in person-centred services, enabling early detection, optimizing medication management, supporting caregivers, and linking people with dementia to formal services. This viewpoint also argues for urgent policy reform, pharmacy curriculum updates, and public-private partnerships to formally integrate dementia care into community pharmacy practice. These steps are essential to build a scalable, compassionate support system for millions of affected people with dementia and their caregivers.
Keywords: Community Pharmacy; Community Pharmacist; Dementia; Alzheimer's Disease; Caregiver Burden; India; Deprescribing; Public Health